Immunochip analysis identifies novel susceptibility loci in the human leukocyte antigen region for acquired thrombotic thrombocytopenic purpura. (3rd December 2016) - Mancini, I.; Ricaño‐Ponce, I.; Pappalardo, E.; Cairo, A.; Gorski, M. M.; Casoli, G.; Ferrari, B.; Alberti, M.; Mikovic, D.; Noris, M.; Wijmenga, C.; Peyvandi, F.; et al.
Abstract : Essentials Genetic predisposition to acquired thrombotic thrombocytopenic purpura (aTTP) is mainly unknown. Genetic risk factors for aTTP were studied by Immunochip analysis and replication study. Human leukocyte antigen (HLA) variant rs6903608 conferred a 2.5‐fold higher risk of developing aTTP. rs6903608 and HLA‐DQB1*05:03 may explain most of the HLA association signal in aTTP. Click to hear Dr Cataland's presentation on acquired thrombotic thrombocytopenic purpura Summary: Background: Acquired thrombotic thrombocytopenic purpura (TTP) is a rare, life‐threatening thrombotic microangiopathy associated with the development of autoantibodies against the von Willebrand factor‐cleaving protease ADAMTS‐13. Similarly to what has been found for other autoimmune disorders, there is evidence of a genetic contribution, including the association of the human leukocyte antigen (HLA) class II complex with disease risk. Objective: To identify novel genetic risk factors in acquired TTP. Patients/Methods: We undertook a case–control genetic association study in 190 European‐origin TTP patients and 1255 Italian healthy controls by using the Illumina Immunochip. Replication analysis in 88 Italian cases and 456 controls was performed with single‐nucleotide polymorphism (SNP) TaqMan assays. Results and conclusion: We identified one common variant (rs6903608) located within the HLA class II locus that was independently associated with acquired TTP at genome‐wide significance and conferred a 2.6‐fold increased risk of developing a TTP episode (95% confidence interval [CI] 2.02–3.27, P = 1.64 × 10 −14 ). We also found five non‐HLA variants mapping to chromosomes 2, 6, 8 and X that were suggestively associated with the disease: rs9490550, rs115265285, rs5927472, rs7823314, and rs1334768 (nominal P ‐values ranging from 1.59 × 10 −5 to 7.60 × 10 ‐5 ). Replication analysis confirmed the association of HLA variant rs6903608 with acquired TTP (pooled P = 3.95 × 10 ‐19 ). Imputation of classic HLA genes followed by stepwise conditional analysis revealed that the combination of rs6903608 and HLA‐DQB1*05:03 may explain most of the HLA association signal in acquired TTP. Our results refined the association of the HLA class II locus with acquired TTP, confirming its importance in the etiology of this autoimmune disease.